Colonization of the Lowland by Slovak ethnicity. The case of the landscape research in Vojlovica (Serbia) - Žabenský, Marián; Letavayová, Silvia (Studia Etnologiczne i Antropologiczne, 2018)
The paper deals with the issue of cultural landscape research with emp‑ hasis on the changes caused by the colonization by Slovak and other ethnic groups. Some parts are focused on defining the methodology of cultural landscape research (multi-temporal analysis of cultural-landscape layers) and its subsequent application in the studied area—the example of Vojlovica village, which is now part of the town of Pančevo in Serbia. The paper also deals with the issue of cultural geography and the retrospective influence of Slovak ethnicity on the landscape. Traditional material and spiritual culture is a reflection of human action in the country and the result of the relationship triangle: landscape—culture—history.